Redefining latent tuberculosis. (September 2011) - Sridhar, Saranya; Pollock, Katrina; Lalvani, Ajit
TB remains a public health problem worldwide, in part due to latent TB infection that serves as a global reservoir of potential disease. In the 20th century, the natural history of TB was defined by clinical symptoms, the tuberculin skin test and chest x-ray. The last decade witnessed the invention and application of IFN-γγ release assays and newer immunological tools that enabled a re-appraisal of the natural history of TB. Here, we review the conventional understanding of latent TB and recount how immunology has redefined latent TB as a spectrum of pathogen burden and host immune control. We discuss recent and future advances in the fields of TB immunology and diagnostics that will improve public health strategies to control TB.